Quality Optimisation of Electronic-Based Government Systems (SPBE) Through the Application of the COBIT Framework in Tangerang Regency - Rahany Aulia , Tiara; Annisa Aulia Zahra , Annisa; Anggi Pangestu , Wanda; Nita Kurniawan, Ajeng; Avrillia, Andien; Dwi Ardiansyah, Achmad; Said, Moh (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The implementation of the COBIT (Control Objectives for Information and Related Technologies) framework is one of the effective approaches to improve the quality of Electronic Based Government Systems (EBS). This study aims to evaluate the implementation of COBIT 2019 in Tangerang Regency to optimize the quality of SPBE. The methodology used is a descriptive study with qualitative methods, involving interviews and observations as primary data collection techniques, and analysis of related documents as secondary data. The results showed that the implementation of COBIT 2019 was able to improve the efficiency and effectiveness of public services through better risk management, system integration, and improved information security. However, some aspects such as adjustments to the scale of the organization and technology adoption strategies still require further improvement. Thus, this study provides recommendations for improving technology adoption strategies and adjusting IT procurement models to suit operational and business needs in Tangerang Regency.